(x+5)^2+(x-10)^2=2x^2

  • +10х+25+-20х+100=
    +10х-20ч=-100-25
    -10х=-125
    х=-125:(-10)
    х=12,5
  • Выражение: (x+5)^2+(x-10)^2=2*x^2
    Решаем по действиям:
    1. (x+5)^2=x^2+10*x+25
    2. (x-10)^2=x^2-20*x+100
    3. x^2+x^2=2*x^2
    4. 10*x-20*x=-10*x
    5. 25+100=125
    6. 2*x^2-2*x^2=0
    —————>
     x^2+10*x+25+(x-10)^2-2*x^2=0
     2*x^2+10*x+25-20*x+100-2*x^2=0
    2*x^2-10*x+125-2*x^2=0
    2*x^2-10*x+125-2*x^2=0
    -10*x+125=0
    Решаем относительно x: x=-(-125)/10=125/10=25/2~~12.5. 
    Ответ:12,5;



See also: